2019
DOI: 10.1108/lhs-10-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Nursing shared governance at hospitals – it’s Finnish future?

Abstract: Purpose The purpose of this study is to describe council structure, its benefits, supportive and obstructive factors and developmental needs as a part of shared governance in a university hospital. Design/methodology/approach This is a descriptive study, where semi-structured interviews with 12 nurses was conducted in 2014 and documents from 75 council meetings from 2009 to 2014 were gathered and analyzed. Qualitative content analysis method was used on the data. Findings The study hospital has been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…One very clear findings is that Finnish nurse managers expect a shift towards shared governance in health care organisations. Several studies have shown that shared governance increases staff's work engagement and empowerment (Olender et al., 2020), improves clinical outcomes (Moreno et al., 2018), enhances patient care, harmonizes nursing practices and enables informed decision‐making (Kanninen et al, 2019). Shared governance is still rarely implemented in Finnish hospitals, but some preliminary results are promising (Kanninen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One very clear findings is that Finnish nurse managers expect a shift towards shared governance in health care organisations. Several studies have shown that shared governance increases staff's work engagement and empowerment (Olender et al., 2020), improves clinical outcomes (Moreno et al., 2018), enhances patient care, harmonizes nursing practices and enables informed decision‐making (Kanninen et al, 2019). Shared governance is still rarely implemented in Finnish hospitals, but some preliminary results are promising (Kanninen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that shared governance increases staff's work engagement and empowerment (Olender et al., 2020), improves clinical outcomes (Moreno et al., 2018), enhances patient care, harmonizes nursing practices and enables informed decision‐making (Kanninen et al, 2019). Shared governance is still rarely implemented in Finnish hospitals, but some preliminary results are promising (Kanninen et al, 2019). Our results indicate that nurse managers want changes to the traditional leadership culture, and regard the new generation of nurses as ready for such change too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brooks-Cleator et al [27], in his studies on transculturality and governance, focus on the importance of the nurse in establishing a culture of safety. The involvement of nurses in social action committees has achieved a great impact on the everyday problems of people [28], highlighting the importance of their participation in decision making [29]. When the nurse is involved in the different parts of the healthcare process (management and nursing care), better results are achieved [30], communication is enhanced, together with collaboration between the different professional groups, innovation, organizational commitment and retention of staff [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that nursing personnel in Finland are likely to be dissatisfied with the nursing process and their ability to obtain feedback from their nurse leaders. They also reportedly regard their managers' transformational leadership qualities as moderate and their nurse directors as distant (6,5,7).…”
Section: Introductionmentioning
confidence: 99%